Dissociation and Reassembly of Escherichia coli Outer Membrane and of Lipopolysaccharide, and Their Reassembly onto Flagellar Basal Bodies - DePamphilis, M. L. (1971)
Purified lipopolysaccharide vesicles dissociate when treated with ethylenediaminetetraacetic acid (EDTA) and then reassemble when dialyzed against Mg(2+). Purified outer, lipopolysaccharide membrane (L membrane) is partially dissociated by treatment with EDTA and fully dissociated upon further treatment with Triton X-100. Both the partially and fully dissociated L membrane can be reassembled by dialysis against Mg(2+). Reassembly of lipopolysaccharide or L membrane in the presence of intact flagella results in specific attachment of flagellar basal bodies to vesicles via the L and sometimes the M ring. Lipopolysaccharide and L membrane appear to be composed of substructures bound together by both Mg(2+) (divalent cation)-mediated and hydrophobic bonds.